Welfare of families who have children with disabilities through empowering the establishment of a curtain stitch business group - Siregar, Hairani; Utama, Fajar (Talenta Publisher, 2020)
This Community Service program is one of the efforts made so that families of children with disabilities have a good source of income. The care of children with disabilities is different from other ordinary children. Children with disabilities need special protection, especially from their families. Caring for children with disabilities is very expensive, until children with disabilities get their basic rights as children. With this service program, children with disabilities can grow and develop like other ordinary children. The training was conducted by forming a curtain-tailing group from the Medan Polonia Women's Community (KPMP). From the results of this training, all group members can measure, sew and install pleated curtains and ring styles. This training gives parents who have children with disabilities have economic resources to continue a good life without having to leave their children at home alone.